Approaches to neuromodulation for schizophrenia. Issue 7 (14th December 2017) - Gault, Judith M; Davis, Rachel; Cascella, Nicola G; Saks, Elyn R; Corripio-Collado, Iluminada; Anderson, William S; Olincy, Ann; Thompson, John A; Pomarol-Clotet, Edith; Sawa, Akira; Daskalakis, Zafiris J; Lipsman, Nir; et al.
Abstract : Based on the success of deep brain stimulation (DBS) for treating movement disorders, there is growing interest in using DBS to treat schizophrenia (SZ). We review the unmet needs of patients with SZ and the scientific rationale behind the DBS targets proposed in the literature in order to guide future development of DBS to treat this vulnerable patient population. SZ remains a devastating disorder despite treatment. Relapse, untreated psychosis, intolerable side effects and the lack of effective treatment for negative and cognitive symptoms contribute to poor outcome. Novel therapeutic interventions are needed to treat SZ and DBS is emerging as a potential intervention. Convergent genetic, pharmacological and neuroimaging evidence implicating neuropathology associated with psychosis is consistent with SZ being a circuit disorder amenable to striatal modulation with DBS. Many of the DBS targets proposed in the literature may modulate striatal dysregulation. Additional targets are considered for treating tardive dyskinesia and negative and cognitive symptoms. A need is identified for the concurrent development of neurophysiological biomarkers relevant to SZ pathology in order to inform DBS targeting. Finally, we discuss the current clinical trials of DBS for SZ, and their ethical considerations. We conclude that patients with severe symptoms despite treatment must have the capacity to consent for a DBS clinical trial in which risks can be estimated, but benefit is not known. In addition, psychiatric populations should have access to the potential benefits of neurosurgical advances.